The importance of RET-directed therapy in patients with RET- rearranged non-small cell lung cancer - Yoh, Kiyotaka (Translational Cancer Research; Vol 6, Supplement 7 (October 24, 2017): Translational Cancer Research, 2017)
Non-small cell lung cancer (NSCLC) has been recognized as a heterogeneous set of diseases according to oncogenic gene alterations level, such as sensitizing EGFR mutations, ALK rearrangements, or ROS1 rearrangements (1). Specific molecularly targeted therapies are effective in NSCLC patients harboring sensitizing EGFR mutations, ALK or ROS1 rearrangements, with response rates of approximately 60% and median progression-free survival of over 10 months (2-4). RET is a proto-oncogene that codes for a transmembrane protein belonging to the receptor tyrosine kinases family (5). In 2012, RET rearrangements were identified as new oncogenic alterations occurring in 1% to 2% of patients with NSCLC (6-9). It is reported that RET rearrangements has tumor-driving activity in vitro and in vivo. RET can partner with different genes in NSCLC, and KIF5B is the most common fusion partner in NSCLC. To date, several other genes including CCDC6, NCOA, TRIM33, CUX1, KIAA1468, KIAA1217, and FRMD4A, have been identified as other fusion partners of RET in NSCLC patients. RET rearrangements tend to be found in younger patients, female, never or former light smokers, and in patients with lung adenocarcinomas (10). A few case reports reported that cabozantinib and vandetanib, which are multi-targeted tyrosine kinase inhibitor exhibiting RET kinase activity, have antitumor activity in patients with RET-rearranged NSCLC (11-13).